2023
DOI: 10.1039/d2sm01468h
|View full text |Cite
|
Sign up to set email alerts
|

A multi-stimulus-responsive bionic fish microrobot for remote intelligent control applications

Abstract: In nature, all creatures have their unique characteristics that allow them to adapt to the complex and changeable living environments. In recent years, bionic fish has attracted increased attention from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Certainly, the landscape of small-scale robotics is adorned with a plethora of elegant technologies that empower these diminutive marvels. Notable examples include the catalytic artificial muscle-based insect-scale robot 9 , magnetic millirobot 10 , jet-based microswimmers 11 , Marangoni effect-based microbots 12 , and a myriad of others 11 . These small-scale enabling technologies have significantly expanded the repertoire of motion forms and capabilities attainable by small-scale robots.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the landscape of small-scale robotics is adorned with a plethora of elegant technologies that empower these diminutive marvels. Notable examples include the catalytic artificial muscle-based insect-scale robot 9 , magnetic millirobot 10 , jet-based microswimmers 11 , Marangoni effect-based microbots 12 , and a myriad of others 11 . These small-scale enabling technologies have significantly expanded the repertoire of motion forms and capabilities attainable by small-scale robots.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to environmental applications, Yang et al prepared fishlike microrobots that respond to multiple stimulants. They demonstrated that the controllability and flexibility of their multistimulus-responsive bionic fish microrobots could enable them to overcome complex tasks and limitations in liquid environments . Similarly, Ahmed et al designed microsized superparamagnetic particles inspired by neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic micro-/nanomotors with autonomous functionalities are of great interest due to their unique motion behavior, especially for active targeted delivery in biomimetic and intelligent transportation. However, the effective actuation and manipulation of micro-/nanomotors is prevented by some limiting factors, such as the low Reynolds number regime where viscosity and Brownian motion occur. To overcome the limitations of swimming, considering that all living systems can adapt to complex and variable living environments with their unique characteristics, many studies have focused on bioinspired micro-/nanosystems, such as the swimming of fish, opening and closing of flowers, and crawling of snakes while designing multifunctional platforms that actively respond to dynamic environmental factors. In addition, the nature-inspired systems have been combined with fundamental concepts, including the Marangoni effect (such as pH, temperature, magnetic field, electric field, ultrasonic field, and light field), self-diffusiophoresis, self-electrophoresis, and bubble propulsion, to stimulate and actuate micrometer-sized systems in a liquid environment. ,, Single-stimulated micromotors are not suitable for complex environments, where complex movements cannot be achieved. In fact, multiple-stimulus-stimulated micromotors have begun to attract more and more attention than single-stimulated ones for active targeting due to their capability of overcoming various biological barriers (blood, cell membrane, tumor interstitial matrix, blood–brain barrier, mucosa, and other body fluids). , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations